Prosedur Pengembalian dan Pemulihan Kerugian Negara Akibat Tindak Pidana Korupsi - Sandi Herintus Kabba; I Made Arjaya; Made Minggu Widyantara (Warmadewa Press, 2022)
Corruption is an extraordinary crime whose eradication must be carried out in an extraordinary manner according to the procedures for returning and recovering state losses due to corruption. This study aims to analyze how the process of carrying out recovery and refund of state losses by prosecutors in corruption crimes and discusses efforts to recover and recover state losses due to corruption. The method used is normative legal research. This research approach is a conceptual and literature approach, with the primary legal sources coming from legislation and decisions, while the secondary legal sources come from legal journals and law books. Data collection is done by collecting data and summarizing. The result of the procedure for returning and recovering state losses due to corruption is in accordance with the procedures, namely the corruption eradication law and other regulations. Efforts to recover and recover state losses due to corruption by maximizing the return of state losses by confiscation, tracing the assets of the convict, the authority of the KPK Prosecutor must be regulated firmly and clearly. Researchers suggest that the government should provide adequate facilities and infrastructure for the Prosecutor's Office and the KPK in order to maximize the eradication of corruption.